Evasão e permanência no ensino superior : o caso do curso de secretariado executivo (Campus IV/UFPB) - Andrade, Anne Angely Guedes (2024)
This research aims to analyse the factors contributing to attrition and retention in the Executive Secretariat course. The study will be conducted at the Center for Applied Sciences and Education (CCAE) on the UFPB Campus IV in Mamanguape, located on the northern coast of Paraíba. Our study is grounded in the works of researchers such as Branco (2020), Silva (2017), and others. Regarding methodology, our research will be qualitative and quantitative.We will analyze the course for the past ten years by interviewing current final- year and former students who did not complete the Executive Secretariat degree. To gather the necessary information, we recorded and transcribed the interviews using open-ended and closed-ended questions. Considering the context of the expansion and regionalization of higher education and the importance of ensuring access and academic success.We have identified a scarcity of literature addressing attrition and retention in this specific course. Therefore, we believe this research will contribute significantly to the field, aiding in understanding these phenomena and enabling the institution to establish goals to address or reduce the number of dropouts.We hope that the results will provide the Center with the necessary tools to develop effective policies to reduce attrition and strengthen student retention.